Dosis de ruminaza (bazofia) en las características vegetativas y rendimiento del forraje del Pennisetum sp. Cuba 22 en Zungarococha, Perú- 2023 - Monteluiz Guillen, Duglas Michael (2023)
The use of solid waste such as swill or better known as ruminaza for soil fertilization is one of the alternatives that the Faculty of Agronomy of the National University of the Peruvian Amazon has been researching with the title: “DOSE OF RUMINAZA (SLEEP) IN THE VEGETATIVE CHARACTERISTICS AND FORAGE YIELD OF Pennisetum sp. CUBA 22 IN ZUNGAROCOCHA, PERU- 2023”, a Completely Randomized Block Design was used, having as treatments T0 (discharge), T1 (10 tons of ruminaz/ha), T2 (20 tons of ruminaz/ha) and T3 ( 30 tons of ruminaza/ha) and four repetitions, reaching the following conclusions: That as the doses of ruminaza increase, the values of the dependent variables increase in our edaphoclimatic conditions of the region. The plant height was 1.66 meters. with T3 (30 tons ruminaza/ha). In green matter of 4.41 kg/m2, and dry matter of 1.06 kg/m2 with the T3 treatment (30 tons ruminase/ha). The green matter of leaves per square meter of 1.63 and stems of 2.78 kg/m2, with the T3 treatment (30 tons ruminase/ha). Yield of green matter kg/ha of 44,075 kilos per hectare, with treatment T3.